Reducing tower fatigue through modelling and analysis of pitch-to-stall, back twist blade, for floating offshore wind turbines. - Ward, Dawn (Cranfield University, 2020)
The negative effects of anthropogenic climate change has led to an increase in electricity generated from renewable energy sources. Within this, offshore wind is currently one of the fastest growing markets, and industry is now looking towards the role that floating offshore wind turbines (FOWT) may play in the future. However, FOWT are often subjected to increased tower loads, up to 1.6 times those experienced by their fixed-to-seabed counterparts. Reducing these loads would help to decrease the costs of this fledgling technology, by diminishing the tower strengthening requirements. In the present work, as a possible technological solution to reduce the above mentioned loads, a variable speed, variable pitch-to-stall (VSVP-S) control strategy, is proposed for wind turbines. The 5 MW turbine is applied to both a semi-submersible and a spar floating platform, as these floaters both suffer from increased tower fore-aft oscillations. The VSVP-S control configuration avoids negative damping by design, allowing higher controller gain settings and hence a more regulated power output, than a pitch-to-feather controlled floating scenario. The FOWTs are further altered to incorporate back twisted blades, to decrease the blade bending moment response. This was seen to decrease the tower fore-aft moment range, creating an increase in the turbine tower life expectancy, when compared to their respective feather base models. To predict the overall tower axial fatigue life, the frequency of anticipated wind speeds are required. The likely occurrence of the different wind speed cases was accounted for through a weighted analysis. This took account of the distribution of probability of occurrence at three mean turbulent wind speeds: 8, 13 and 18 m/s. FOWT analysis highlighted trends in terms of back twist angle initiation point and magnitude were similar for both VSVP-S models (i.e. semi-submersible and a spar floating platforms). When a back twist angle to -6° at the tip was imposed, starting at 75% along the blade length, increases in the tower axial fatigue life of 10.2% for the semi-submersible and 18.8% for the spar were achieved, with the VSVP-S controlled turbines, compared to their feather controlled counterparts.
EngD in Renewable Energy Marine Structures
Keywords: Floating offshore wind turbine (FOWT); tower fore-aft moments; negative damping; blade flapwise moment; tower axial fatigue life; spar; semi-submersible